Criminalizing Coercive Control Within the Limits of Due Process - Sheley, Erin (2021)
The sociological literature on domestic abuse shows that it is more complex than a series of physical assaults. Abusers use “coercive control” to subjugate their partners through a web of threats, humiliation, isolation, and demands. The presence of coercive control is highly predictive of future physical violence and is, in and of itself, also a violation of the victim’s liberty and dignity. In response to these new understandings the United Kingdom has recently criminalized nonviolent coercive control, making it illegal to, on two or more occasions, cause “serious alarm or distress” to an intimate partner that has a “substantial effect” on their “day-to-day activities.” Such a vaguely drafted criminal statute would raise insurmountable due process problems under the U.S. Constitution. Should the states wish to address the gravity of the harms of coercive control, however, this Article proposes an alternative statutory approach. It argues that a state legislature could combine the due process limits of traditionally enterprise-related offenses such as fraud and conspiracy with the goals of domestic abuse prevention to create a new offense based upon the fraud-like nature of coercively controlling behavior. It argues that the most useful legal framework for defining coercive control is similar to that of common law fraud, and that legislatures should adapt the scienter requirements of fraud to the actus reus of coercive control. In so doing, this Article also argues that it is risky for legislatures to punish gender-correlated offenses with specialized legal solutions, rather than recognizing the interrelationship between such offenses and other well-established crimes